Strategies for establishing networking with partner schools for implementing lesson study in Indonesia - Nurwidodo, Nurwidodo; Hendayana, Sumar; Hindun, Iin; Sarimanah, Eri (Jurnal Pendidikan Biologi Indonesia, 2018)
Lesson Study for Learning Community (LSLC) contains two terminologies underpinning one another. There are many difficult challenges when the plan to create LSLC surfaces. Therefore, strong motivation and precise implementation strategies are of urgency. One of the ways is by developing networking of LSLC between universities and partner schools. The LSLC program will become powerful when it is done collaboratively in a form of strong partnership connected by networks. Writing this article aims to describe strategies for establishing networking with partner schools for implementing lesson study in Indonesia. This review article uses literature comparison study methods and use content analysis. In order for LSLC to manifest and become successful, resourcing and utilizing the partnership with schools are required. In a partnership with schools in order to implement LSLC, both parties must share the same need, which is facing the challenge with the willingness to cooperate for solving the problem. Cooperation with partner schools needs to be nurtured to become networking so that the benefits and the spirit of cooperation in solving problem double fold. Networking with partner schools can be implemented and can function well when the management of this networking conforms to shared needs, nurtures cooperation and mutual respect, gives and takes equally, and also promotes fair acceptance, support, independence, and discipline.